Устройство формирования сигналов для контроля радара некогерентного рассеяния - Емельянов, Леонид Яковлевич; Богомаз, Александр Викторович; Бравичев, Богдан Романович (НТУ "ХПИ", 2016)
С целью контроля измерения параметров ионосферы методом некогерентного рассеяния (НР) предложено устройство формирования сигналов для тестирования приемных и обрабатывающих систем радара НР. Требования к нему выработаны на основе анализа характеристик НР сигнала. Устройство позволяет оперативно контролировать основные параметры радиотехнических систем радара и точность определения параметров ионосферы, таких как температуры ионов и электронов, скорость движения ионосферной плазмы, а также тестировать и оптимизировать алгоритмы и программы обработки шумоподобных сигналов.

The signal generation device for testing radio receiving and processing systems of the incoherent scatter (IS) radar is proposed to check the ionosphere parameters measurements by IS technique. Requirements to it were developed based on analysis of the characteristics of the IS signal. The device consists of a generator of the signal spectrum in the low frequency range on the basis of PC and synthesizer of the monitoring signals. It allows to synthesize continuous or radio pulse pilot signal of several types: harmonic signal with specified frequency shift relative to the work radar frequency, noise-like signal with uniform spectrum in selected frequency band, the signal with programmable parameters that is similar to the IS signal for different states of the ionosphere. The device allows to operatively check main parameters of radar systems, monitoring the accuracy of the ionospheric parameters such as the ion and electron temperatures and the ionospheric plasma drift velocity, test and optimize the noise-like signal processing algorithms and programs.
Device for generation of signals for testing the incoherent scatter radar
Keywords: доплеровское смещение; спектр случайного сигнала; обработка сигнала; устройство контроля; скорость движения плазмы; incoherent scatter radar; Doppler shift; signal processing; testing device; plasma drift velocity